Implementation of Restorative Justice for Misdemeanor Offenders with the Bajanjang Naik Batanggo Turun Customary Approach - Trisno Raharjo; Laras Astuti; Susan Dwi Saputri (Kosmik Hukum, 2025)
The large number of criminal acts committed by criminals who crowd the prisons. The application of criminal sanctions in the form of imprisonment has resulted in prisons becoming increasingly full.  The form of punishment that places more emphasis on punishing the perpetrator of the crime causes attention to be paid to the victim and other parties to be neglected, a new approach is needed that does not only focus on the victim but also on all parties involved, such as the restorative justice approach which emphasizes that the resolution of criminal cases does not have to be based on a spirit of revenge, but can be achieved through peace, where the perpetrator and victim can reach an agreement to restore the relationship and overcome the psychological and social impacts arising from the crime. This study uses a normative legal research type with a conceptual and legislative approach. The source of legal materials uses primary, secondary and tertiary legal materials obtained from literature studies and obtained through interviews with sources related to this study, namely Ninik Mamak Suku, namely the Head of the Sikabau Nagari Customary Council. The analysis of legal materials used in this study uses qualitative descriptive. The results of this study provide an overview of the application of restorative justice using the traditional bajanjang naik batanggo turun approach to customary crimes in Minangkabau. The results of this study are that the approach is carried out hierarchically with the principle of deliberation and consensus.